2021
DOI: 10.1029/2021gl094128
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Coral Reef Resilience Through Successive Marine Heatwaves

Abstract: Marine heatwaves have increased in frequency and magnitude with devastating consequences for ocean ecosystems (Smale et al., 2019). Tropical reef-building corals have been particularly hard hit, with significant global declines linked to thermal stress (Hughes et al., 2018). As the oceans continue to warm, model projections of coral reef futures have become increasingly dire (van Hooidonk et al., 2016).Yet, amidst widespread declines are indications that some coral populations have the ability to survive risin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
0
25
1
Order By: Relevance
“…Changes in bleaching susceptibility in response to previous stress exposures were also reported from other regions across the globe, particularly after recurrent bleaching events (Pratchett et al 2013;Hughes et al 2019;Fisch et al 2019;Gintert et al 2018;Fox et al 2021;Guest et al 2012). The bleaching severity of three major coral genera (Acropora, Pocillopora, and Porites) in the Great Barrier Reef (GBR) was reported to be much lower than expected during the 2002 bleaching despite higher and longer temperature stress compared to the previous 1998 bleaching event.…”
Section: Acquired Tolerance In Adult Coralsmentioning
confidence: 73%
“…Changes in bleaching susceptibility in response to previous stress exposures were also reported from other regions across the globe, particularly after recurrent bleaching events (Pratchett et al 2013;Hughes et al 2019;Fisch et al 2019;Gintert et al 2018;Fox et al 2021;Guest et al 2012). The bleaching severity of three major coral genera (Acropora, Pocillopora, and Porites) in the Great Barrier Reef (GBR) was reported to be much lower than expected during the 2002 bleaching despite higher and longer temperature stress compared to the previous 1998 bleaching event.…”
Section: Acquired Tolerance In Adult Coralsmentioning
confidence: 73%
“…By extension, the absence of these coral-rich, uninhabited islands from this analysis may influence our finding of no difference in reef builder cover between inhabited and uninhabited islands. However, a recent study by Fox et al (2021) reported mean coral cover of <20% in 2018 from three of these uninhabited Phoenix Islands present in the Smith et al (2016) study. Thus, recent coral cover at uninhabited reefs of the Phoenix Islands seem to align with observed values reported here in the U.S.-affiliated islands and atolls in the central Pacific, suggesting that these reefs are not insulated from coral loss.…”
Section: Discussionmentioning
confidence: 84%
“…However, coral thermal stress tolerance varies widely and can be influenced by the temperature regimes of specific locations (Morikawa and Palumbi, 2019;Cornwell et al, 2021;Logan et al, 2021). Selective mortality through successive heatwaves may shape coral responses to subsequent warming events (Fox et al, 2021) where repeated heatwaves may improve the 'ecological memory' of corals to further enhance thermal tolerance for future climate projections (Hackerott et al, 2021). Consequently, reconciling spatial patterns of coral thermal tolerance and their associated drivers is critical for improving projections of coral survival in the future.…”
Section: Introductionmentioning
confidence: 99%